SOCIAL MEDIA INFLUENCERS AND IMAGE OF NATIONS: APPROPRIATING THE ENERGIES OF SELECT NIGERIAN SMIS TO BOOST NIGERIA’S GLOBAL REPUTATION - Usua, Ntiense; Ijah, Isomgboawaji Ntente Ruth (Brazilian Creative Industries Journal, 2023)
Nigerian has been grappling with battered image since independence but more so since the return of the nation to civilian rule in 1999. The various governments, conscious of the importance of good reputation at a time interdependence among nations is a necessity, have been embarking on image laundry activities but largely, the nation is perceived as a corrupt, insecure, lawless and economically weak nation with people who are not to be trusted for serious partnership. This has worsened with the negative stereotype of developing nations by global media. But developments in the entertainment industry—music, movie, comedy and related content making enterprises—which have produced several influencers, indicate that notwithstanding negative portrayal, social media influencers have made contents that have popularized and portray them in positive ways and through that, endear themselves to global audiences, using the social media. This gives rise to the need to find out whether the visibility of Social Media Influencers could be exploited to change the negative image of the country and to find out how the social media influencers could help in this regard, among other objectives. Using the library research approach, the paper analyses the relationship between the media and national image, the role of social media in image building as well as examine how popular social media influencers through their contents can boost Nigeria’s image. The SMIs analyzed were selected based on news publications of their popularities on the different social media platforms such as TikTok, Facebook, Instagram and Twitter. The publications include top 10 lists of most popular people on these social media platforms and most popular viral contents by Nigerians in the past few years leading up to 2022. Supported by the precepts of perception and technological determinism theories respectively, the paper notes that updating of the perception of the country can occur through the interaction with the observed, in this case the SMIs and that technology (social media) can be leveraged upon to solve Nigeria’s image problem. It concludes that if the SMIs could make positive impacts as demonstrated by their large followings at the global stage, they could deploy their energies to create positive image for Nigeria. It recommends the deliberate involvement of SMIs as forces that can cause a positive update of the perspective of the global audience about Nigeria in the effort to change the narrative that has been built around the nation and indeed change the image of the country in order to rebrand and reposition it in the comity of nations.